2020
DOI: 10.1088/1742-5468/aba7b1
|View full text |Cite
|
Sign up to set email alerts
|

Run-and-tumble particle in inhomogeneous media in one dimension

Abstract: We investigate the run-and-tumble particle (RTP), also known as persistent Brownian motion, in one dimension. A telegraphic noise σ(t) drives the particle which changes between ±1 values at certain rates. Denoting the rate of flip from 1 to −1 as R 1 and the converse rate as R 2 , we consider the position-and direction-dependent rates of the form R 1 (x) = |x|

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 77 publications
1
44
0
Order By: Relevance
“…The distribution of an RnT particle is captured by the propagator P (x, t) = (φ(x, t) + ψ(x, t)) φ(x 0 , 0) , where the system is initialised at t 0 = 0 with a right-moving particle at x 0 [27,60]. Diagrammatically, the particle distribution is (D.1)…”
Section: Appendix C Some Propagators In Closed Formmentioning
confidence: 99%
“…The distribution of an RnT particle is captured by the propagator P (x, t) = (φ(x, t) + ψ(x, t)) φ(x 0 , 0) , where the system is initialised at t 0 = 0 with a right-moving particle at x 0 [27,60]. Diagrammatically, the particle distribution is (D.1)…”
Section: Appendix C Some Propagators In Closed Formmentioning
confidence: 99%
“…where the notation L s→t denoted the inverse Laplace transformation as indicated in Eq. (18). Using the inverse Laplace transformations…”
Section: Small Z Behaviour Of Fα(z)mentioning
confidence: 99%
“…Several studies on heterogeneous diffusive processes (HDPs) have revealed anomalous scaling of the mean squared displacement (MSD) and weak ergodicity breaking between time averaged and ensemble averaged MSDs [10][11][12][13][14][15][16]. Persistent properties of HDPs have also been investigated in [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Over the recent few years, this model has been substantially studied and a variety of results are known. Examples include -position distribution in free space as well as in confining potential [21][22][23][24][25][26][27], condensation transition [28][29][30], persistent properties [31][32][33], extremal properties [34,35], path functionals [34,36], current fluctuations [37], interacting multiple RTPs [27,[38][39][40][41], etc.…”
Section: Introductionmentioning
confidence: 99%